2012
DOI: 10.1007/s00601-011-0297-7
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Corrections in ν A DIS and Their Compatibility with Global NPDF Analyses

Abstract: We perform a global χ 2 -analysis of nuclear parton distribution functions using data from charged current neutrino-nucleus (ν A) deep inelastic scattering (DIS), charged-lepton-nucleus ( ± A) DIS, and the Drell-Yan (DY) process. We show that the nuclear corrections in ν A DIS are not compatible with the predictions derived from ± A DIS and DY data. We quantify this result using a hypothesis-testing criterion based on the χ 2 distribution which we apply to the total χ 2 as well as to the χ 2 of the individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…A compromise solution between ν-A and ± -A data can be found only if the full correlated systematic errors of the ν-A data are not used and all the statistical and systematic errors are combined in quadrature thereby neglecting the information contained in the correlation matrix. This conclusion underscores the fundamental differences [41] of the nCTEQ analysis with some of the other contemporary analyses [40,266] using different statistical methods. These other analyses suggest the ν-A and ± -A DIS data can be statistically consistent and relates the discrepancies to possible energy- In particular they cite non-negligible differences in the absolute normalization between different neutrino data sets that, they claim, are large enough to prevent a tension-free fit to all data simultaneously.…”
Section: Comparison Of the ± A And νA Nuclear Correction Factorsmentioning
confidence: 68%
See 1 more Smart Citation
“…A compromise solution between ν-A and ± -A data can be found only if the full correlated systematic errors of the ν-A data are not used and all the statistical and systematic errors are combined in quadrature thereby neglecting the information contained in the correlation matrix. This conclusion underscores the fundamental differences [41] of the nCTEQ analysis with some of the other contemporary analyses [40,266] using different statistical methods. These other analyses suggest the ν-A and ± -A DIS data can be statistically consistent and relates the discrepancies to possible energy- In particular they cite non-negligible differences in the absolute normalization between different neutrino data sets that, they claim, are large enough to prevent a tension-free fit to all data simultaneously.…”
Section: Comparison Of the ± A And νA Nuclear Correction Factorsmentioning
confidence: 68%
“…These studies by nCTEQ [41] have shown a strong indication that there is indeed a difference between the ± A and the νA nuclear correction factors. An analysis by the HKN [263] group also finds some inconsistencies between ν(ν) and charged-lepton data and most recently, a direct comparison [156] of F νF e 2 with F ± F e 2 structure functions observed a clear (≈ 20%) difference between ν(ν) and charged lepton scattering off Fe for the structure functions at low x.…”
Section: Nuclear Correction Factors For Neutrino Nucleus Scatteringmentioning
confidence: 95%
“…3 See Refs. [10,11], and also references therein. 4 We have added CTEQ6.1+EPS09 as CTEQ6.1 was the baseline used for the EPS09 fit.…”
Section: Cross Section Correlationsmentioning
confidence: 99%
“…In the other approach nuclear PDFs are directly parameterized by analyzing the experimental data, i.e without using nucleon PDFs or nuclear correction factor. This approach has been recently used by nCTEQ [13,14] group in getting F EM 2A (x, Q 2 ), F W I 2A (x, Q 2 ) and F W I 3A (x, Q 2 ), who have collectively analyzed the charged lepton-A DIS and DY p − A dilepton production data sets [13] to determine the nuclear correction factor in the electromagnetic sector, and have performed an independent analysis for the ν l (ν l ) − A DIS data sets [14]. It has been concluded by them that the nuclear medium effects in F EM 2A (x, Q 2 ) are different from F W I 2A (x, Q 2 ) specially in the region of low x.…”
Section: Introductionmentioning
confidence: 99%